Analisis Disiplin Kerja Pegawai Negeri Sipil di Sekretariat Daerah Kantor POLDA Sumatera Utara - Annisa, Moza; Ramadhani, Sri (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Employee performance must be considered because it is one of the keys to success. If an agency carries out agency activities with poor performance, the agency's image will be unfavorable. According to Law Number 5 of 2014 Concerning the Principles of Civil Service, it gives the understanding that a Civil Servant is every citizen of the Republic of Indonesia who has fulfilled the specified requirements, is appointed by an authorized official and entrusted with other state duties, and is given employee benefits based on statutory regulations. -applicable invitations. In this case, discipline is a process used to deal with performance problems.